Profitability, Leverage, Liquidity, Carbon Emissions, on Coal Company Value: The Role of Corporate Governance - Sylvia Marcellina; Novia Rosita; Rilla Gantino (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study aims to analyze the influence of profitability, leverage, liquidity, and carbon emission disclosure on firm value, and examine the role of corporate governance as a moderating variable in coal subsector companies listed on the Indonesia Stock Exchange for the 2022-2025 period. Firm value is proxied by Price to Book Value (PBV), while profitability is measured by ROA, leverage by DER, liquidity by CR, carbon emission disclosure by CEDI, and corporate governance by the proportion of independent commissioners. The study used a quantitative approach with panel data and a purposive sampling method, resulting in 108 observations. Testing was conducted using a Random Effects model with robust standard errors to address heteroscedasticity. The results show that leverage has a significant positive effect on firm value, while profitability, liquidity, and carbon emission disclosure have no significant direct effect. Corporate governance has a significant negative direct effect, but it strengthens the effect of carbon emission disclosure on firm value. Conversely, corporate governance weakens the effect of leverage and liquidity on firm value and does not moderate the effect of profitability. These findings suggest that corporate governance plays a significant role in shaping market responses to financial and non-financial information in the coal industry.